Prevalence of exhaustion symptoms and associations with school level, length of work experience and gender: a nationwide cross-sectional study of Swedish principals - Roger Persson; Ulf Leo; Inger Arvidsson; Carita Håkansson; Kerstin Nilsson; Kai Österberg (BMC, 2021)
Abstract Background While poor mental health and psychiatric disorders attributed to stressful work conditions are a public health concern in many countries, the health consequences of the occupational stress experienced by school principals is an understudied issue. Although current data is lacking, some research suggests that principals have a stressful work situation that eventually may lead to burnout and exhaustion disorder, thus negatively affecting the ability of principals to function as leaders. To gauge the situation in Sweden, and as a basis for future preventive actions, we examined to what extent principals displayed signs of exhaustion and whether the prevalence rates of exhaustion differed across school levels, length of work experience as a principal, and gender. Methods Principals (N = 2219; mean age 49 years [SD 7 years]; 78% women) working at least 50% in pre-schools, compulsory schools, upper secondary schools or adult education completed a cross-sectional web survey entailing two validated inventories: The Karolinska Exhaustion Disorder Scale (KEDS) and the Lund University Checklist for Incipient Exhaustion (LUCIE). Data was analysed using traditional non-parametric methods. Gender stratification achieved covariate balance when analysing school level and length of work experience. Results Altogether, 29.0% of the principals met the exhaustion criteria in KEDS. The prevalence rates for the four LUCIE-steps of increasing signs of exhaustion were: no signs of stress, 48.8%; weak signs of stress, 25.6%; clear signs of stress but no exhaustion, 15.4%; possible exhaustion disorder, 10.2%. Compared with male principals, female principals reported more signs of possible exhaustion disorder in both LUCIE and KEDS. School level was not associated with reports of exhaustion symptoms in neither LUCIE nor KEDS. Among male principals, length of work experience was associated with exhaustion symptoms in KEDS. Conclusions A large group of Swedish principals working in pre-schools, compulsory schools, upper secondary schools or adult education displayed a symptomatology of signs of exhaustion that if sustained might lead to poor health. This observation suggests that education authorities, or other relevant stakeholders, ought to take some form of preventive action. However, effective combinations of individual, group, organisational, and/or societal preventive activities remain to be identified and tested.